The Macroeconomic Impact of Scaled-Up Aid : The Case of Niger - Sacerdoti, Emilio (IMF Working Papers; Working Paper ;, 2009)
We develop a simple macroeconomic model that assesses the effects of higher foreign aid on output growth and other macroeconomic variables, including the real exchange rate. The model is easily tractable and requires estimation of only a few basic parameters. It takes into account the impact of aid on physical and human capital accumulation, while recognizing that the impact of the latter is more protracted. Application of the model to Niger-one of the poorest countries in the world-suggests that if foreign aid as a share of GDP were to be permanently increased from the equivalent of 10 percent of GDP in 2007 to 15 percent in 2008, annual economic growth would accelerate by more than 1 percentage point, without generating significant risks for macroeconomic stability. As a result, by 2020 Niger's income per capita would be 12.5 percent higher than it would be without increased foreign aid. Moreover, the higher growth would help Niger to cut the incidence of poverty by 25 percent by 2015, although the country will still be unable to reach the Millennium Development Goal of poverty reduction (MDG 1).